Pengaruh latihan passing variasi fun shooting game terhadap ketepatan shooting pada pemain ssb paokmotong ku 16-17 tahun - Moh zul haji al-subhi; Ali Muhaimin; Jamaludin (Jurnal Pengetahuan dan Pendidikan, 2025)
The purpose of this researcher is to determine the effect of shooting training with Passing and Move in Grid and Passing Relay Race on shooting accuracy in SSB Paokmotong KU players aged 16-17 years and to find out which is more effective. This research is an experimental research, the design used in this research is an experimental research using the design "Two Group Pretest-Posttest Design. The instrument used is the test and measurement of Shooting Accuracy. The subjects of this study with a population of 141 players, the sampling technique used a purposive sample and those who met the criteria were 18 children. The data analysis technique used the t test with a significance level of 5%. Based on the results of the study, the t test on shooting practice with a running ball obtained a t-count value of 8.854> t table (2.306), and a p value (0.012) <0.05, with a percentage increase of 38.87%. While the results of the t test of shooting practice with a back pass obtained a t-count value of 3.250> t table (2.306), and a p value (0.000) <0.05, with a percentage increase of 15.11%. The results can be concluded that there is an Effect of Passing Practice Variations of Fun Shooting Games on Shooting Accuracy in Players SSB Paokmotong Ku 16-17 Years. With the results above, the most effective is the Passing Variation Fun Shooting Game training method.